A Generalized Reliability Mechanism with minimum -Replica by PRCR (International Journal of Engineering and Computer Science, 2017)
The rapid progress of technology and large scale use of internet has resulted in generation of an enormous amount of data .In the recent years, cloud computing has become popular among various fields like information technology and various business enterprises. The fundamental use of the cloud now a days is for storing information and sharing the resources. Cloud is another way to store expensive measure of information. Cloud provides the storage space and offering to use this information to various clients. Additionally it is technique for pay according to we utilize. The two principle concerns in current cloud storage systems are providing the reliable data and storage cost. To ensure data reliability, current cloud systems uses multi-replica strategy (typically three replicas), which incurs a huge storage space, on the effect it leads to more storage cost for data-intensive applications in the cloud. To minimize the storage space, in this paper we proposed a cost effective data reliability mechanism called Proactive Replica Checking for Reliability (PRCR) by using a generalized data reliability model. PRCR guarantees the reliability with the reduced replication factor, which can likewise reduce the storage cost for replication based methodologies. Contrasting to the traditional three – replica strategy, PRCR can diminish the storage space utilization by one-third to two-thirds of the current storage space, thus fundamentally bringing down the storage cost.